(untitled) (Scientific journal of the Fergana State University, 2023)
Increases in blood glucose levels lead to many diseases, to normalize blood glucose levels, many synthetic drugs are used, despite their therapeutic properties, they also have side effects. In this article, in order to introduce into practice natural analogues of medicinal products with medicinal properties in plants without side effects, the hyperglycemic properties of medicinal plants which regulate blood glucose levels are studied.